2009
DOI: 10.1152/japplphysiol.00086.2009
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between body mass index and adiposity in prepubertal children: ethnic and geographic comparisons between New York City and Jinan City (China)

Abstract: Body mass index (BMI) is often used as a surrogate estimate of percent body fat in epidemiological studies. This study tested the hypothesis that BMI is representative of body fatness independent of age, sex, ethnicity, and geographic location in prepubertal children. The study sample included a total of 605 prepubertal children (275 girls and 330 boys) of which 247 were Chinese from Jinan, Shandong, Mainland China, and 358 children were from various ethnic backgrounds in New York City (NYC): 121 Caucasians, 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 38 publications
3
25
0
Order By: Relevance
“…Similar trend has also been reported in a number of studies for Chinese children [22-24]. In Chinese traditional opinion, boys tend to receive extra attention in early life, and are expected to be strong, while girls should be slim.…”
Section: Discussionsupporting
confidence: 84%
“…Similar trend has also been reported in a number of studies for Chinese children [22-24]. In Chinese traditional opinion, boys tend to receive extra attention in early life, and are expected to be strong, while girls should be slim.…”
Section: Discussionsupporting
confidence: 84%
“…In a comparative study of body composition in Asian and Caucasian young adult females, results showed a similar PBF (31%) for Taiwanese women aged 20 to 29, with a similar BMI (23.7 kg/m 2 ) that we observed [18]. In a comparative study of prepubertal children from China and New York City, similar correlation patterns were observed with Chinese girls having the highest PBF and lowest BMI compared to girls of other geographic and racial origins [34]. In a large cross-sectional study of adiposity from a medical practice in Manhattan, BMI misclassified 48% of women when DXA was used to validate BMI [35].…”
Section: Discussionsupporting
confidence: 70%
“…Similarly, the Pearson correlations of BMI with PBF and TBF were 0.83 and 0.93, respectively, in a sample of 3-12-year-old children from New York City (White, African American, Chinese and Korean) and China. 11 In that study, for a given level of BMI, Asians (from China and Korea) had higher levels of PBF than White and African Americans. In our study, we found that boys from India had significantly higher PBF than boys in several other countries, but Chinese boys and girls did not stand out as being different than children from other counties.…”
Section: Discussionmentioning
confidence: 78%